Instantaneous Kinematics Analysis via Screw-Theory of a Novel 3-CRC Parallel Mechanism. (15th June 2016) - de la Torre, Hussein; Rodriguez-Leal, Ernesto
This paper presents the mobility and kinematics analysis of a novel parallel mechanism that is composed by one base, one platform and three identical limbs with CRC joints. The paper obtains closed-form solutions to the direct and inverse kinematics problems, and determines the mobility of the mechanism and instantaneous kinematics by applying screw theory. The obtained results show that this parallel robot is part of the family 2R1T, since the platform shows 3 DOF, i.e .: one translation perpendicular to the base and two rotations about skew axes. In order to calculate the direct instantaneous kinematics, this paper introduces the vectormh, which is part of the joint velocity vector that multiplies the overall inverse Jacobian matrix. This paper compares the results between simulations and numerical examples using Mathematica and SolidWorks in order to prove the accuracy of the analytical results.